Effect of Exchange Rate Volatility on Exports in Nigeria: A Test of Cochrane-Orcutt Technique - Sa’idu, Bello Malam (International Journal of Management and Sustainability, 2015)
This paper examines the dynamic effects of exchange rate fluctuations on exports in Nigeria. To achieve the set objectives, classical least square and Cochrane-Orcutt technique were applied. Results revealed that exchange rate volatility and foreign income have positive and significant effect on exports, while relative prices exert negative and significant effect on exports. This implies that, a unit rise in exchange rate volatility and foreign income, coincidentally both lead to increase in exports by eightfold. Consequently, government should strengthen the Naira to minor spirals, attract foreign income flow, and promote export goods, among others. Foreign income flow could be attracted via private investment of export goods, transforming them to semi-processed form thereby improving exports prices, values and volume in the country.